2020
DOI: 10.3390/su12114691
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Fertilizer Value Chain in Mozambique

Abstract: Mozambique is characterized by low agricultural productivity, which is associated with low use of yield-enhancing agricultural inputs. Fertilizer application rate averaged 5.7 kg ha−1 in Mozambique during the period 2006 to 2015, considerably low by regional targets, yet constraints that affect fertilizer use have not been thoroughly investigated. This study examined the constraints on fertilizer value chains in Mozambique to contribute to fertilizer supply chain strengthening. We used a combination of multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In their study on fertilizer usage by smallholders in Burkina Faso, Koussoubé and Nauges ( 2016 ) found that fertilizer usage was generally profitable at prevailing prices, even at low investment levels, and concluded that supply constraints via local inputs markets were likely inhibiting adoption. Zavale et al ( 2020 ) found that the growth of the fertilizer industry in Mozambique was limited by demand side factors (i.e., limited effective demand from farmers) and supply side factors (including high transactions costs). Both of these factors are known to have strong spatial expressions (Minten et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their study on fertilizer usage by smallholders in Burkina Faso, Koussoubé and Nauges ( 2016 ) found that fertilizer usage was generally profitable at prevailing prices, even at low investment levels, and concluded that supply constraints via local inputs markets were likely inhibiting adoption. Zavale et al ( 2020 ) found that the growth of the fertilizer industry in Mozambique was limited by demand side factors (i.e., limited effective demand from farmers) and supply side factors (including high transactions costs). Both of these factors are known to have strong spatial expressions (Minten et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Application of different organic and inorganic fertilizers can increase crop yields by over 50%, depending on the nutritional need of the particular plant being grown [58]. Inorganic fertilizers (NPK) with high N content were reported to increase maize (Zea mays L.) crop yields by 76.2% in the southern part of Africa, which makes them recommendable for application in other crop faming [59]. In 2017, it was estimated that 181.9 million metric tons (Mt) of fertilizer was applied in crop farming globally, and maize was recognized as the greatest consumer of fertilizer in agriculture [60].…”
Section: Nitrate Contamination From Inorganic Fertilizersmentioning
confidence: 99%
“…However, up to 50% of N and 90% of P in inorganic fertilizer are not assimilated by plants and run off from the crop fields during irrigation and rain to be deposited in the nearby water bodies [67,68]. Commercial fertilizers and pesticides for crop farming contribute to most NO 3 − traced in contaminated drinking water sourced from surface and groundwater systems, which causes environmental hazards that threaten both terrestrial and aquatic life [59,69]. The Nitrogen quantity in fertilizer is estimated to increase by 172% by the year 2050, which poses the risk of further elevating NO 3 − concentrations in the environment [64].…”
Section: Nitrate Contamination From Inorganic Fertilizersmentioning
confidence: 99%
“…On the one hand, industry organizations will supply high-quality fertilizers needed by smallholders free of charge or at a price below the market price. Fertilizers with better effect, easier absorption, and environmental protection will improve crop quality and yield and improve soil quality [87,88]. Farmers will get higher per mu yield with lower input of production factors, optimize the land allocation efficiency and improve the per mu profit [89].…”
Section: Poverty Reduction Mechanism Of Smallholders' Participation In Agricultural Value Chain Activitiesmentioning
confidence: 99%